Relationship between Ecosystem Knowledge and Locus of Control with Intention to Act in MAN on Environment of Sukabumi District - Solihin, Solihin; Sigit, Diana Vivanti; Miarsyah, Mieke (International Journal for Educational and Vocational Studies, 2020)
Intention to act of students is an interpretation of knowledge of ecosystems and locus of control. This study aims to look at the relevance of students' intention to act which is analyzed through ecosystem knowledge and locus of control. Research on the intention to act to date has been developed because of the problem of deterioration in people's behavior in interacting in the ecosystem. The method used in this research is descriptive qualitative, with a sample of 203 respondents. The technique used is multistage random sampling. The instrument used is a questionnaire for locus of control and intention to act data collection. Multiple choice instrument in retrieving data on ecosystem knowledge of students. This study concluded that there was a relationship between ecosystem knowledge and locus of control with the intention to act.